Archaeal glycolipid adjuvanted vaccines induce strong influenza-specific immune responses through direct immunization in young and aged mice or through passive maternal immunization. Issue 47 (8th November 2019) - Stark, Felicity C.; Akache, Bassel; Ponce, Amalia; Dudani, Renu; Deschatelets, Lise; Jia, Yimei; Sauvageau, Janelle; Williams, Dean; Jamshidi, Mohammad P.; Agbayani, Gerard; Wachholz, Kristina; Harrison, Blair A.; et al.
Abstract: Vaccine induced responses are often weaker in those individuals most susceptible to infection, namely the very young and the elderly, highlighting the need for safe and effective vaccine adjuvants. Herein we evaluated different archaeosome formulations as an adjuvant to the H1N1 influenza hemagglutinin protein and compared immune responses (anti-HA IgG and hemagglutination inhibition assay titers) as well as protection to an influenza A virus (strain A/Puerto Rico/8/1934 H1N1) homologous challenge to those generated using a squalene-based oil-in-water nano-emulsion, AddaVax™ in a murine model. The impact of age (young adult vs aged) on vaccine induced immune responses as well as the protection in pups due to the transfer of maternal antibodies was measured. Overall, we show that archaeal lipid based adjuvants can induce potent anti-HA responses in young and aged mice that can also be passed from vaccinated mothers to pups. Furthermore, young and aged mice immunized with archaeal lipid adjuvants as well as pups from immunized mothers were protected from challenge with influenza. In addition, we show that a simple admixed archaeosome formulation composed of a single sulfated glycolipid namely sulfated lactosylarchaeol (SLA; 6′-sulfate-β-D-Gal p -(1, 4)-β-D-Glc p -(1, 1)-archaeol) can give equal or better protection compared to AddaVax™ or the traditional antigen-encapsulated archaeosome formulations.